AN EXPERIMENTAL STUDY OF MECHANICAL EFFECT IN CLEANING PROCESS - Koc, Yusuf; Heperkan, Hasan Alpay (YILDIZ TECHNICAL UNIV, 2015)
Cleaning is the process of using water and detergent to remove soil, rust stains or other deposits from surfaces. The cleaning performance is the most important competitive factor. The main parameters that influence the cleaning performance are chemicals, water temperature, cleaning time and mechanical impact on the surfaces. This paper is related with mechanical impact of cleaning processes. A Water Jet Test Apparatus was used to measure the force, generated by a jet of water as it strikes the surface under various experimental conditions. Measured values were between 0.09 and 0.49 N, these were a function of flow rates, angle of impact surface, distance from nozzle to impact surface and cross-sectional area of nozzle. The results showed that the higher flow rate provides a greater impact force with the same nozzle. If the cross-sectional areas of nozzles increase, the water jet impact forces decrease on similar flow rate values. For same experimental conditions, the jet impact force increases with angle of impact surfaces, reaches a maximum value on 90 degrees. The most effective parameter on force was impact of flow rate. As a result of tests, effectiveness of impact of flow rates were 59%, effectiveness of cross-sectional areas of nozzles were 21% and effectiveness of angle of impact surfaces were 15%. The impact of distance from nozzle to surface had limited effect on the jet force.
Keywords: Mechanical impact; water jet; jet force; impact surface; nozzle; flow ratec; SURFACES; REMOVAL; Engineering